Integrated effect of water regimes and nitrogen levels on productivity of transplanted rice (Oryza sativa) and wheat (Triticum aestivum) under rice-wheat cropping system: Field and simulation study - GOYAL, V; SINGH, A K; MISHRA, A K; PARIHAR, S S (The Indian Journal of Agricultural Sciences, 2018)
Field experiment was consecutively conducted for two years on deep alluvial clay loam soil (Typic haplustept) with three levels of water regimes and four levels of nitrogen in rice-wheat cropping system. Integrated effect of water and nitrogen levels depicted the rice and wheat grain yield of 3.55 and 3.41 Mg/ha respectively. Individually, grain yield increased by 104.9 and 70.3% respectively for rice and wheat with increasing N levels from 0-180 kg/ha. A reduction of 9.6 and 19.7% in grain yield was observed with change in treatment of water regimes from W1 to W2 and W1 to W3 in rice. The corresponding values for wheat were 6.3 and 13.7%, respectively. The simulation study, carried out by calibrating and validating the CropSyst model, showed the simulation yields were in agreement with observed yields as was evident by high correlation coefficient (0.87 - 0.96) and modeling efficiency (0.79 - 0.95) at all water regimes and nitrogen levels for biomass and grain yield. Also, the root mean square error (RMSE) for biomass and grain yield was 5 and 9% of the observed mean in rice which was 3 and 18% for wheat indicating that the model is accurate in predicting these two initial parameters. The model was tested for accuracy in determining the crop parameters by conducting sensitivity analysis which depicted that the above ground biomass conversion, optimum mean daily temperature and phenological degree days needs more accuracy in simulation. Pooled experimental data of the two years showed that substantial water saving can be done but the yield was reduced by 9.6 and 19.7% in rice and 6.3 and 13.7% in case of wheat which can be neglected at the time of rising global water stress.